Digital Transformation of MSMEs: A Study on the Impact and Motives of Using Third-Party E-Commerce Platforms: Profitable or Not? - Sabrina Liemansyaputri; Endi Sarwoko; Cosmas Gatot Haryono (Eduvest - Journal of Universal Studies, 2025)
With the development of technology, the lifestyle of today's society has changed. Therefore, it encourages MSMEs to keep up with the technological developments in order to be able to survive in undergoing competition in this new era. This article will discuss the impact and motives of MSME’s in using third party e-commerce platforms. Where most other articles discuss the positive side of the presence of third-party e-commerce platforms for MSME’s. Therefore, the purpose of this article is to deeply understand the impact of digital transformation from both the positive and negative sides of MSME’s in using third-party e-commerce platforms. In addition, this research will identify the factors that influence the success of MSMEs in carrying out digital transformation, as well as the challenges faced by MSME’s in carrying out the digital transformation process in business. This research will use the Uses and Gratifications Theory (UGT) approach to better understand the motives of MSME’s to join or digitize their business by using third party e-commerce platforms. This research uses a descriptive qualitative method by conducting in-depth interviews and observations as primary data and e-journal sources, e-books, websites as secondary data. Deep interviews were conducted with 11 (eleven) MSME owners/managers in Makassar City who have different characteristics such as business size (based on the Central Bureau of Statistics), product type, and length of use of third-party e-commerce platforms. This study found that the digitization of MSME’s through third-party e-commerce platforms has complex dynamics.